Predictors Financial Management Behavior of MSMEs in Bandung - Ridwan, Ridwan; Berliani, Kartika; Akbar, Rifqi Farisan (International Journal of Marketing & Human Resource Research, 2025)
The objective was to identify the financial management practices of MSMEs in Bandung, West Java, Indonesia, using quantitative method with a Likert scale for measurement of variables. The independent variables include financial literacy, financial attitude, financial experience, personality, and locus of control, while the dependent variable is the finance management behavior. The analysis yielded the following findings: financial literacy, financial attitude, and locus of control exerted a detrimental influence on financial management behavior, whereas personality demonstrated a favorable impact on the same. Conversely, financial experience was observed to exert no discernible effect on financial management behavior. The results demonstrate that all variables in this study exert a simultaneous influence on financial management behavior. The findings of this study may prove useful as a reference point for a variety of stakeholders, particularly the Government of Bandung, in formulating policies aimed at enhancing the financial management practices of MSMEs